Funcionalidad familiar y rendimiento académico en los estudiantes de primero de bachillerato de la Unidad Educativa Emigdio Esparza Moreno - Aroca Tenorio, Marcia Jessenia (2022)
The purpose of this research study was to determine the influence of family functionality on academic performance in first-year high school students of the Emigdio Esparza Moreno Educational Unit, maintaining a population of 70 students, the sample is framed by a non-probabilistic sample. For convenience with a total of 35 students. Based on a quantitative research approach, type of correlational research, non-experimental design. The techniques and instruments used to collect information on the family functionality variable are psychometric tests such as the FF-SIL test and the family satisfaction scale, and for the academic performance variable, a survey to validate self-perception of their academic performance and the analysis of the report card. According to all the methodology used, it was possible to determine that there is an influence between the two variables studied, since it can be identified that the 15 students belonging to dysfunctional and severely dysfunctional families have low academic performance except for 4 students, compared to the students belonging to functional and moderately functional families, all have a good academic performance, among them are those who achieve and master the required learning. For which, this research had a significant impact since it was possible to identify problems that are affecting the school life of the students and according to this, the educational entity can be guided to propose different solutions that allow solving the problem and thus strengthen the teaching process and learning of the study subjects.